1994
DOI: 10.1021/bi00182a006
|View full text |Cite
|
Sign up to set email alerts
|

DNA Mismatch Binding and Incision at Modified Guanine Bases by Extracts of Mammalian Cells: Implications for Tolerance to DNA Methylation Damage

Abstract: Two activities involved in separate pathways for correcting G.T mispairs in DNA have been assayed on duplex substrates containing modified guanine bases. The first, the G.T mismatch incision activity, is specifically involved in short-patch repair of mispairs arising via deamination of 5-methylcytosine. The second activity can be detected by its ability to bind to G.T mispairs and may initiate correction by a long-patch mechanism. 6-Thioguanine and O6-methylguanine paired with thymine were efficiently incised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
68
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 38 publications
14
68
0
Order By: Relevance
“…Loss of DNA mismatch repair has been reported to produce drug resistance, directly by impairing the ability of the cell to detect adducts in its DNA that mimic base mismatches, and indirectly by increased gene mutation rates, leading to a mutator phenotype. For example, loss of mismatch repair causes high-level resistance to the antimetabolite 6-thioguanine, 20 moderate levels of resistance to the methylating agent N-methyl-NЈ-nitro-N-nitrosoguanidine 21 and low-level resistance to the platinum-containing drugs cisplatin and carboplatin. 7 All these agents cause cell death via apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of DNA mismatch repair has been reported to produce drug resistance, directly by impairing the ability of the cell to detect adducts in its DNA that mimic base mismatches, and indirectly by increased gene mutation rates, leading to a mutator phenotype. For example, loss of mismatch repair causes high-level resistance to the antimetabolite 6-thioguanine, 20 moderate levels of resistance to the methylating agent N-methyl-NЈ-nitro-N-nitrosoguanidine 21 and low-level resistance to the platinum-containing drugs cisplatin and carboplatin. 7 All these agents cause cell death via apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was reported that loss of MLH1 results in resistance to 6-thioguanine 20 and 5-fluorouracil. 8 Gemcitabine is incorporated as difluorodeoxycytidine-monophosphate (dFdCMP), resulting in inhibition of chain elongation due to the inability of dFdCMP to be excised by exonucleases.…”
Section: Discussionmentioning
confidence: 99%
“…That resistance to temozolomide in this cell line was not dependent upon AGT activity was confirmed with both single and repeat dosing studies, in which depletion of AGT by 06-BG did not afford an increase in temozolomide cytotoxicity (Figures 4 and 6). This 'tolerance' to methylation may be attributable to loss of the mismatch repair pathway, which would normally generate DNA strand breaks and thereby induce cell death during the futile attempt to find a complementary base for o6-methylguanine (Griffin et al, 1994 Modrich, 1986): hMSH2 (Fishel et al, 1993) and GTBP/pl60 (Drummond et al, 1995;Palombo et al, 1995). This structure interacts with another heterodimer consisting of hPMS2 and hMLH1 proteins (Li and Modrich, 1995), which are homologues of the E. coli MutL repair protein (Grilley et al, 1989).…”
mentioning
confidence: 99%
“…Several interesting mechanistic details have been reported, however. It is known that mammalian mismatch repair systems use one DNA repair complex to repair A:C, T:T or T:C mismatches but have at least two separate repair complexes for G:T or G:U mispairs putatively arising from endogenous 5-methylcytosine or cytosine deamination events, respectively (7,8). One pathway to correct G:T mispairs appears confined primarily to CpG sequences in mammalian cells (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that mammalian mismatch repair systems use one DNA repair complex to repair A:C, T:T or T:C mismatches but have at least two separate repair complexes for G:T or G:U mispairs putatively arising from endogenous 5-methylcytosine or cytosine deamination events, respectively (7,8). One pathway to correct G:T mispairs appears confined primarily to CpG sequences in mammalian cells (7,8). It is now evident that all combinations of mismatches can be repaired in mammalian cells; however, G:T mispairs are corrected with much higher efficiency than others (7,9).…”
Section: Introductionmentioning
confidence: 99%